Adolescent Mothers’ Sexual, Contraceptive, and Emotional Relationship Content With the Fathers of Their Children Following a First Diagnosis of Sexually Transmitted Infection - Hensel, Devon J. (2011)
PURPOSE: A sexually transmitted infection (STI) diagnosis may profoundly change the meaning of adolescent women’s relationships, particularly when the relationship involves a shared child. This study explored the sexual, contraceptive, and emotional characteristics of sexual partners with whom adolescent women had and did not have children in the 3 months after the first STI diagnosis. METHODS: Adolescent women (n = 387; age: 14–17 years at enrollment) were tested quarterly for STI and completed partner-specific items on emotional and sexual relationship content. We used nonparametric statistics (SPSS/18.0) to compare these characteristics between partners with whom these adolescent women did (n = 20) or did not (n = 118) share a child. RESULTS: Rates of condom use at last sex, overall condom use, and condom insistence were lower with sexual partners involving shared children as compared with childless sexual partners. Relationship status, commitment to partner, and using no method of contraception were more common in parous sexual relationships as compared with nulliparous sexual relationships after an STI. CONCLUSIONS: After an STI, adolescent women have different sexual risk behaviors with the fathers of their children, even after a signal event such as a recent STI diagnosis. Tailored counseling may specifically address the challenges of STI prevention with partners who have the unique status of being the “father of the baby.”